Delignified cellulose-based fibers extracted from natural plant materials, and materials containing such fibers

Through chemical extraction methods, lignin and hemicellulose from natural plant materials were removed, and strong and tough cellulose-based large fibers were successfully extracted, solving the problems of low extraction efficiency and fiber damage in the prior art, and achieving efficient and economical fiber extraction effect.

CN115698426BActive Publication Date: 2025-03-04UNIV OF MARYLAND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180042253.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-14
Filing Date
2021-04-21
Publication Date
2025-03-04
Estimated Expiration
2041-04-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extract strong and tough large cellulose-based fibers from natural plant materials, and traditional mechanical extraction methods are prone to fiber damage and mechanical properties.

Method used

Using a "top-down" chemical extraction method, natural plant materials are treated with alkaline solutions and other chemicals through a two-step delignification process, removing lignin and hemicellulose, thereby releasing large cellulose-based fibers and improving the mechanical properties of the fibers by rinsing and drying.

Benefits of technology

It realizes efficient extraction of strong and tough large cellulose-based fibers from natural plant materials, improves the mechanical properties of the fibers, and is simple in process and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115698426B_ABST
    Figure CN115698426B_ABST
Patent Text Reader

Abstract

The block of natural plant material is subjected to one or more chemical treatments to remove substantially all of the lignin therefrom, thereby allowing the extraction of delignified cellulose fibers. For example, the natural plant material can be a grass, such as bamboo or gladiolus. The extracted fibers are then dried to densify the structure, thereby improving mechanical properties. In some embodiments, the extracted fibers can be used as structural materials alone or in combination with other materials. For example, the extracted fibers can be embedded in a polymer or concrete, infiltrated with a polymer or concrete, coated with a polymer or concrete, or otherwise combined with a polymer or concrete to form a composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 013,401, filed on April 21, 2020, entitled “Strong, Delignified Fibers, Methods of Making and Using the Same,” and U.S. Provisional Application No. 63 / 065,994, filed on August 14, 2020, entitled “Decoupled Fluidic Transport Materials and Methods of Preparing the Same,” each of which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to the processing of naturally occurring cellulose-based materials and, more particularly, to the extraction of delignified cellulose-based fibers from fibrous plant materials and their use in structural materials and devices. Summary of the invention

[0004] Embodiments of the disclosed subject matter provide a simple, cost-effective "top-down" method for making strong, tough fibers by chemically extracting cellulose-based macrofibers (e.g., at least 5 μm in diameter) from natural plant materials. For example, the natural plant material can be bamboo, gladiolus, reed, or other grasses. In some embodiments, the manufacturing method includes a two-step delignification process. In the first step, the natural plant material is treated with an alkaline solution of one or more chemicals to partially remove lignin and hemicellulose from the plant material. In the second step, the partially delignified plant material is treated with a different solution of one or more chemicals to further remove lignin and hemicellulose. Alternatively, in some embodiments, the manufacturing method includes a single-step delignification process using a single solution of one or more chemicals. In either case, the delignified plant material can be rinsed and stirred, thereby causing the cellulose-based macrofibers to release from each other. In some embodiments, the subsequent drying of the released macrofibers can result in self-densification, which can further improve the mechanical properties of the macrofibers. The resulting large fibers can be used as independent structural components (eg, ropes, cables, etc.) or as reinforcements in matrices or substrates (eg, to form composite materials).

[0005] Any of the various innovations disclosed herein may be used in combination or alone. This summary is provided to introduce a selection of concepts in a simplified form, which concepts will be further described in the detailed description below. This summary is not intended to identify the key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter. The above and other objects, features and advantages of the disclosed technology will become more apparent from the detailed description below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Embodiments will be described below with reference to the accompanying drawings, which are not necessarily drawn to scale. Where applicable, certain elements may be simplified or not illustrated to help illustrate and describe the basic features. Throughout the accompanying drawings, the same reference numerals represent the same elements.

[0007] 1 is an exemplary process flow diagram of a method for extracting and using delignified cellulose-based macrofibers from natural plant materials, according to one or more embodiments of the disclosed subject matter.

[0008] 2A is a simplified schematic diagram of delignified cellulose-based macrofibers extracted from natural plant material, according to one or more embodiments of the disclosed subject matter.

[0009] 2B-2D illustrate exemplary configurations of a plurality of delignified macrofibers as a bundle, a one-dimensional array, and a two-dimensional array, respectively, according to one or more embodiments of the disclosed subject matter.

[0010] 3A-3D illustrate exemplary configurations of composite materials incorporating delignified macrofibers arranged in non-woven configurations, biaxial weaves, triaxial weaves, and knitted weaves, according to one or more embodiments of the disclosed subject matter.

[0011] 4A is a simplified schematic diagram showing the infiltration of a polymer into delignified macrofibers to form a composite material according to one or more embodiments of the disclosed subject matter.

[0012] 4B is a simplified schematic diagram illustrating an exemplary apparatus for vacuum assisted resin transfer molding (VARTM) according to one or more embodiments of the disclosed subject matter.

[0013] 5A is a simplified partial cross-sectional view of a natural bamboo segment from which cellulose-based fibers can be extracted, according to one or more embodiments of the disclosed subject matter.

[0014] 5B is a top view of a cross-section of a natural bamboo segment.

[0015] FIG. 5C is an enlarged image of the culm of the natural bamboo segment of FIG. 5B .

[0016] FIG. 5D is a further magnified scanning electron microscope (SEM) image showing the layered microstructure of the culm wall of FIG. 5C .

[0017] FIG. 5E is a SEM image showing a perspective view of a wall portion of a bamboo stem having large fibers and thin-walled cells therein.

[0018] 5F-5G are magnified SEM images of portions of the image of FIG. 5E , showing microfibrils forming macrofibrils and the regions between the microfibrils and the thin-walled cells, respectively.

[0019] FIG5H is a diagram showing the size distribution of microfibers in natural bamboo macrofibers.

[0020] 6A is a simplified schematic diagram showing the composition of a portion of natural bamboo and the extraction of intact macrofibers therefrom by delignification, according to one or more embodiments of the disclosed subject matter.

[0021] 6B-6C are photographs showing natural bamboo after 6 hours and 12 hours, respectively, of a chemical treatment step for delignification according to one or more embodiments of the disclosed subject matter.

[0022] 6D-6E are images of separated cellulose-based macro-scale fibers after a delignification process, according to one or more embodiments of the disclosed subject matter.

[0023] 6F-6G are SEM images showing a top view and a cross-sectional side view, respectively, of a natural bamboo stem.

[0024] 6H-6I are SEM images showing top view and cross-sectional side view, respectively, of a bamboo stem after partial delignification (eg, chemical treatment for 10 hours), according to one or more embodiments of the disclosed subject matter.

[0025] 6J-6K are SEM images showing top and side views, respectively, of macro-scale fibers extracted from bamboo stems by delignification and subsequent drying according to one or more embodiments of the disclosed subject matter.

[0026] 7A-7B are polarized light microscope images and magnified views of cellulose-based macrofibers extracted from bamboo, according to one or more embodiments of the disclosed subject matter.

[0027] 7C-7D are polarized light microscopy images and magnified views of comparative lignocellulose-based macrofibers mechanically extracted from bamboo.

[0028] 8A is a graph comparing stress-strain curves of cellulose-based macro-fibers extracted from bamboo according to an embodiment of the disclosed subject matter, lignocellulose-based macro-fibers mechanically extracted from bamboo, and natural bamboo stems.

[0029] 8B is a graph comparing the tensile strength and Young's modulus of cellulose-based macro-fibers extracted from bamboo according to an embodiment of the disclosed subject matter, lignocellulose-based macro-fibers mechanically extracted from bamboo, and natural bamboo stems.

[0030] 8C is a graph comparing the work to break of cellulose-based macrofibers extracted from bamboo according to an embodiment of the disclosed subject matter, lignocellulosic-based macrofibers mechanically extracted from bamboo, and natural bamboo stems.

[0031] 8D is a graph comparing the tensile strength of cellulose-based macro-fibers having different diameters and a gauge length of 2 cm extracted from bamboo according to an embodiment of the disclosed subject matter.

[0032] 9A is an image of a fabric mat formed from cellulose-based macrofibers extracted from bamboo, according to one or more embodiments of the disclosed subject matter.

[0033] 9B is an image of a fabricated composite material formed by encasing the fabric mat of FIG. 9A in epoxy resin according to one or more embodiments of the disclosed subject matter.

[0034] FIG. 9C is a graph comparing the tensile strength and Young's modulus of the fabricated composite materials of FIG. 9B .

[0035] 10A-10B are images of natural grass and lignocellulose-based macrofibers extracted therefrom, respectively, according to one or more embodiments of the disclosed subject matter.

[0036] 10C-10D are SEM images showing cross-sectional perspective views of natural grass and its thin-walled cells and fibers, respectively.

[0037] 10E is an optical microscope image of lignocellulose-based macrofibers extracted from grass, according to one or more embodiments of the disclosed subject matter.

[0038] FIG. 11A is an image of natural grass before delignification.

[0039] 11B shows an image of the natural grass of FIG. 11A after a first step of partial delignification (left) and a second step of chemical removal (right), according to one or more embodiments of the disclosed subject matter.

[0040] 11C shows an image of the natural grass of FIG. 11A after a first step of complete delignification (left) and a second step of chemical removal (right), according to one or more embodiments of the disclosed subject matter.

[0041] 12 is a graph comparing stress-strain curves of lignocellulose-based macrofibers extracted from grass according to an embodiment of the disclosed subject matter and natural grass leaves. DETAILED DESCRIPTION

[0042] General considerations

[0043] For the purpose of this specification, certain aspects, advantages and novel features of the disclosed embodiments are described herein. The disclosed methods and systems should not be interpreted as limiting in any way. On the contrary, the present disclosure is directed to all novel and non-obvious features and aspects of the various disclosed embodiments, individually and in various combinations and sub-combinations with each other. The methods and systems are not limited to any particular aspect or feature or combination thereof, nor do the disclosed embodiments require any one or more specific advantages or problems solved. The technology from any embodiment or example can be combined with the technology described in any one or more other embodiments or examples. In view of the many possible embodiments to which the principles of the disclosed technology can be applied, it should be recognized that the illustrated embodiments are merely exemplary embodiments and should not be considered to limit the scope of the disclosed technology.

[0044] Although the operations of some disclosed methods are described in a specific, sequential order for ease of presentation, it should be understood that this description includes rearrangement unless the specific language described below requires a specific order. For example, in some cases, the operations described in sequence may be rearranged or performed simultaneously. In addition, for simplicity, the accompanying drawings may not show the various ways in which the disclosed methods can be used in conjunction with other methods. In addition, the description sometimes uses terms such as "provide" or "implement" to describe the disclosed methods. These terms are high-level abstractions of the actual operations performed. The actual operations corresponding to these terms can vary depending on the specific implementation and are easily recognized by those of ordinary skill in the art.

[0045] Unless otherwise stated, the disclosure of numerical ranges should be understood to refer to each discrete point within the range, including endpoints. Unless otherwise stated, all numerals used in the specification or claims to represent component amounts, molecular weights, percentages, temperatures, times, etc. should be understood to be modified by the term "about". Therefore, unless otherwise implied or explicitly stated, or unless the context is correctly understood by a person of ordinary skill in the art to have a more explicit structure, the numerical parameters set forth are approximate values ​​of the desired properties and / or detection limits sought under standard test conditions / methods known to a person of ordinary skill in the art. When directly and explicitly distinguishing an embodiment from the prior art discussed, unless the word "about" is narrated, the embodiment numbers are not approximate. Whenever "substantially", "approximately", "about" or similar language is used in explicit combination with a specific value, unless otherwise explicitly stated, it is expected to be up to and include a 10% change in the value.

[0046] Directional and other relative references may be used to aid in the discussion of the drawings and principles herein, but are not intended to be limiting. For example, certain terms such as "inner," "outer," "upper," "lower," "top," "bottom," "interior," "exterior," "left," "right," "front," "back," "rear," etc. may be used. Where applicable, these terms are used to provide some clarity when dealing with relative relationships, particularly for the embodiments shown. However, these terms do not imply absolute relationships, positions, and / or directions. For example, for an object, the "upper" portion can become the "lower" portion simply by turning the object over. Nonetheless, it is still the same portion and the object is still the same.

[0047] As used herein, "comprising" means "including", and the singular forms "a" or "an" or "the" include plural references unless the context clearly dictates otherwise. The term "or" refers to a single element or a combination of two or more elements of the alternative elements, unless the context clearly dictates otherwise.

[0048] Although there are substitutions for various components, parameters, operating conditions, etc. described herein, this does not mean that these substitutions must be equivalent and / or perform the same. Unless otherwise specified, this does not mean that the alternatives are listed in a preferred order. Unless otherwise specified, any group defined below can be substituted or unsubstituted.

[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. Although methods and materials similar or equivalent to the methods and materials described herein can be used for the practice or testing of the present disclosure, suitable methods and materials are described below. These materials, methods and examples are only illustrative and are not intended to be limiting. The features of the present disclosure theme can be clearly seen from the following detailed description and the appended claims.

[0050] Terminology Overview

[0051] The following explanations of specific terms and abbreviations are provided to facilitate describing various aspects of the disclosed subject matter and to guide those of ordinary skill in the art in practicing the disclosed subject matter.

[0052] Longitudinal growth direction: The direction in which a plant grows from its roots or from its trunk, with the cellulose nanofibers that form the plant's cell walls typically aligned in the longitudinal growth direction. In some cases, the longitudinal growth direction may be generally vertical, or correspond to the direction of its water transpiration flow. This is in contrast to the radial growth direction, which extends outward from the central part of the plant and may be generally horizontal.

[0053] Delignification: removing part (such as at least 50%) or almost all (such as at least 90%) of the naturally occurring lignin from natural plant materials. The lignin content in plant materials before and after delignification can be assessed using techniques known in the art, for example, the National Renewable Energy Laboratory (National Renewable Energy Laboratory, NREL) published Laboratory Analytical Procedure (Laboratory Analytical Procedure, LAP) TP-510-42618 "Determination of Structural Carbohydrates and Lignin in Biomass" version 08-03-2012, and ASTM E1758-01 (2020) published by ASTM International "Standard Test Method for Determination of Carbohydrates in Biomass by High Performance Liquid Chromatography", both of which are incorporated herein by reference.

[0054] Natural plant material: a part of any photosynthetic eukaryotic organism in the plant kingdom grown in its natural state (e.g., a part cut by mechanical means or otherwise). In some embodiments, the natural plant material is a species selected from the Poales order or the Poaceae family. For example, in some embodiments, the natural plant material can be any of bamboo, gladiolus, reed, sugarcane, corn, wheat, rice, jute, hemp, kenaf, ramie, banana, corn, wheat, rice, roselle, rattan, sorghum, sisal, palm, henequene, abaca, pineapple, curaua, yucca, cabuja, screw pine, abaca, or agave. In other embodiments, the natural plant material is a part of any type of fiber plant having naturally formed (e.g., grown) large fibers in a lignin-cellulose matrix.

[0055] Bamboo: Any species of the subfamily Bambusoideae, such as, but not limited to, Moso, Phyllostachys vivax, Phyllostachys viridis, Phyllostachys bambusoides, and Phyllostachys nigra.

[0056] Macrofiber: An elongated structure composed of a plurality of cellulose microfibrils arranged in parallel and having its largest cross-sectional direction (also referred to herein as diameter) in a plane perpendicular to its length, for example in the range of 100 μm to 1 mm inclusive.

[0057] Microfibril: A microscopic-scale elongated structure composed of a plurality of cellulose nanofibers arranged in parallel, and having a diameter in the range of, for example, 1 μm to 10 μm both inclusive.

[0058] Elementary nanofiber: A basic nanometer-scale elongated structure composed of a plurality of polymer molecular chains (eg, 10-36 chains) stacked in a parallel or antiparallel direction, and having a diameter of, for example, 5 nm or less.

[0059] introduce

[0060] Natural plants are primarily composed of cellulose, hemicellulose, and lignin, the contents of which vary depending on the type of plant. Typically, cellulose in natural plant materials is surrounded by a complex matrix of hemicellulose and lignin, which complicates the extraction of cellulosic material from natural plant materials using conventional mechanical techniques. In contrast, embodiments of the disclosed subject matter provide a "top-down" technique that reduces the lignin and hemicellulose content in natural plant materials, but only moderately reduces the cellulose content. Highly selective removal of lignin and hemicellulose allows the extraction of intact, natural cellulose-based macrofibers from plant materials with less damage.

[0061] In some embodiments, the manufacturing method includes a two-step delignification process. In the first step, the natural plant material is treated with an alkaline solution of one or more chemicals to partially remove lignin and hemicellulose from the plant material. In the second step, the partially delignified plant material is treated with a different solution of one or more chemicals to further remove lignin and hemicellulose. Alternatively, in some embodiments, the manufacturing method includes a single-step delignification process using a single solution of one or more chemicals. In either case, the delignified plant material can be rinsed and stirred, resulting in the release of cellulose-based large fibers from each other. In some embodiments, the subsequent drying of the released large fibers can result in self-densification, which can further improve the mechanical properties of the large fibers.

[0062] The extracted delignified macrofibers are composed of aligned and tightly packed cellulose microfibers, so that hydrogen bonds and van der Waals forces are formed between them with almost no structural defects, thereby showing improved mechanical properties. For example, delignified macrofibers with a diameter of 5-1000 μm and a length of 5-200 cm can be constructed, and their tensile strength is at least 0.5 GPa (e.g., more than 1 GPa). In an embodiment, the delignified macrofibers can be used as independent structural components, such as ropes, cables, moisture-activated actuators or springs, woven fabrics, etc. Alternatively or additionally, in some embodiments, the delignified macrofibers are combined with a matrix or substrate (e.g., a polymer or concrete) to form a composite material. In these embodiments, the delignified macrofibers can serve as a reinforcing component of the substrate.

[0063] Method Example

[0064] FIG. 1 shows an exemplary method 100 for extracting and using delignified cellulose-based macrofibers from natural plant materials. In some embodiments, the plant material is bamboo or gladiolus. However, in other embodiments, the plant material can be any other plant with natural cellulose-based macrofibers. For example, the plant material can be other types of natural grasses of the Gramineae or Gramineae family.

[0065] Method 100 may begin at processing block 102, where a piece of natural plant material is provided. For example, providing at processing block 102 may include cutting, removing, or otherwise separating the piece of natural plant material from a parent plant. In some embodiments, the providing may optionally include pre-processing the piece of natural plant material, for example, cleaning to remove any unwanted materials or contaminants in preparation for subsequent processing; forming the natural plant material into a particular shape in preparation for subsequent processing; or any combination thereof.

[0066] Method 100 may proceed to processing box 104, where the natural plant material is subjected to a first chemical treatment to remove at least some lignin therefrom, for example, by immersing the natural plant material (or a portion thereof) in one or more chemical solutions associated with the treatment. In some embodiments, the first chemical treatment may be effective in partially removing (but not completely removing) lignin and hemicellulose from the plant material. In these embodiments, method 100 may proceed to processing box 110 via decision box 106 to remove additional lignin and hemicellulose by subjecting the plant material to a second chemical treatment different from the first chemical treatment. Alternatively, in some embodiments, the first chemical treatment alone may be effective in removing most (e.g., at least 90%) lignin from the plant material. In such embodiments, method 100 may proceed directly to decision box 112 via decision box 106, as described in further detail below. Prior to any second treatment of processing box 110, the plant material may be optionally washed or rinsed at processing box 108, for example, to remove residual chemicals and / or other impurities from the plant material treated with the first chemical treatment. For example, washing of process block 108 may include submerging the plant material (or a portion thereof) in deionized (DI) water.

[0067] In some embodiments, the first chemical treatment, the second chemical treatment, or both may be performed under vacuum, thereby promoting complete penetration of the solution associated with the treatment into the cell walls and lumina of the natural plant material. Alternatively, in some embodiments, the first chemical treatment, the second chemical treatment, or both may be performed under ambient pressure conditions or high pressure conditions (e.g., 6-8 bar). In some embodiments, the first chemical treatment, the second chemical treatment, or both may be performed at any temperature between ambient temperature (e.g., 23° C.) and a high temperature (e.g., 70-160° C.) at which the solution associated with the chemical treatment boils. In some embodiments, the solution may be stirred to promote dissolution of the lignin and hemicellulose matrix, in which the desired cellulose-based macrofibers are embedded.

[0068] In some embodiments, the immersion time for the first chemical treatment, the second chemical treatment, or both may be in any range of 0.1 hours to 96 hours, for example, between 4 hours and 12 hours (including 4 hours and 12 hours). The amount of time immersed in the solution may be a function of the amount of lignin to be removed, the size of the block, the solution temperature, the processing pressure, and / or agitation. For example, less lignin removal, smaller block size, higher solution temperature, higher processing pressure, and agitation may be associated with a shorter immersion time, while more lignin removal, larger block size, lower solution temperature, lower processing pressure, and no agitation may be associated with a longer immersion time.

[0069] In some embodiments, the solution of the first chemical treatment, the second chemical treatment, or both includes an alkaline solution. In some embodiments, the solution of the first chemical treatment, the second chemical treatment, or both may include sodium hydroxide (NaOH), lithium hydroxide (LiOH), potassium hydroxide (KOH), sodium sulfite (Na2SO3), sodium sulfide (Na2S), Na n S (where n is an integer), urea (CH4N2O), sodium bisulfite (NaHSO3), sulfur dioxide (SO2), anthraquinone (AQ) (C 14 H8O2), methanol (CH3OH), ethanol (C2H5OH), butanol (C4H9OH), formic acid (CH2O2), hydrogen peroxide (H2O2), acetic acid (CH3COOH), butyric acid (C4H8O2), formic acid peroxide (CH2O3), acetic acid peroxide (C2H4O3), ammonia (NH3), p-toluenesulfonic acid (p-TsOH), sodium hypochlorite (NaClO), sodium chlorite (NaClO2), chlorine dioxide (ClO2), chlorine (Cl2), or any combination thereof.

[0070] For example, the chemical solution for the first chemical treatment may include, but is not limited to, NaOH, NaOH+Na2SO3, NaOH+Na2S, NaOH+urea, NaHSO3+SO2+H2O, NaHSO3+Na2SO3, NaOH+Na2SO3, Na2SO3+AQ, NaOH+NaHSO3+AQ, NaOH+Na2S+AQ, NaOH+Na2SO3+AQ, NaHSO3+SO2+AQ, Na2SO3+NaOH+CH3OH+AQ, NaHSO3+Na2SO3+AQ, NaOH+Na2S, wherein AQ is anthraquinone, or any of the foregoing with LiOH or KOH instead of NaOH, or a combination thereof. For example, the chemical solution of the second chemical treatment may include, but is not limited to, O2, O3, Cl2, ClO2, H2O2, NaClO2, NaClO, Ca(ClO)2, NaOH+H2O2, O2+H2O2, CHOOH+H2O2, CH3COOH+H2O2, C2H5COOH+H2O2, C3H7COOH+H2O2, or any combination of the foregoing.

[0071] In one non-limiting example, the first chemical treatment may include immersing the natural plant material (or a portion thereof) in a solution comprising potassium hydroxide (KOH) and sodium sulfite (Na2SO3), potassium hydroxide (KOH) and sodium sulfide (Na2S), sodium hydroxide (NaOH) and sodium sulfite (Na2SO3), or a mixture of sodium hydroxide (NaOH) and sodium sulfide (Na2S), and the second chemical treatment may include immersing the plant material (or a portion thereof) in a solution comprising a mixture of hydrogen peroxide (H2O2) and acetic acid (C2H4O2) or formic acid (CH2O2). In another non-limiting example, the first chemical treatment may include immersing a block of natural plant material (or a portion thereof) in formic acid peroxide (CH2O3), and the second chemical treatment may include immersing the block of plant material (or a portion thereof) in a solution comprising sodium hydroxide (NaOH) or potassium hydroxide (KOH).

[0072] In another non-limiting example involving bamboo as a natural plant material, the first chemical treatment may include immersing the bamboo block (or a portion thereof) in a solution of NaOH (e.g., 10 wt%) and Na2SO3 (e.g., 5 wt%) at 70° C. for 4 hours, and the second chemical treatment may include immersing the bamboo block (or a portion thereof) in a solution of H2O2 (e.g., 10 wt%) and acetic acid (e.g., 10 wt%) at 60° C. for 4 hours. In another non-limiting example involving gladiolus as a natural plant material, the first chemical treatment may include immersing the gladiolus block (or a portion thereof) in a solution of NaOH (e.g., 10 wt%) and Na2SO3 (e.g., 5 wt%) at 70° C. for 6 hours, and the second chemical treatment may include immersing the bamboo block (or a portion thereof) in a solution of H2O2 (e.g., 5 wt%) and acetic acid (e.g., 2 wt%).

[0073] The delignification of the first and second chemical treatments, or in some embodiments the first chemical treatment alone, results in the removal of a majority of the lignin (e.g., at least 90%) and / or a majority of the hemicellulose (e.g., at least 90%) from the natural plant material, while retaining a majority (e.g., at least 90%) of the cellulose. For example, after the first and second chemical treatments, the delignified plant material has a lignin content less than or equal to 10 wt% (e.g., ≤5 wt% or ≤3 wt%), a hemicellulose content less than or equal to 10 wt% (e.g., ≤6 wt%), a cellulose content of at least 70 wt% (e.g., ≥85 wt%), or any combination thereof.

[0074] Method 100 can therefore proceed from processing frame 110 or judgment frame 106 to judgment frame 112, where it is determined whether washing or rinsing is required. If washing is required, method 100 can proceed to processing frame 114, where rinsing is performed. For example, the delignified plant material can be partially or completely immersed in one or more rinsing solutions. The rinsing solution can be a solvent, such as but not limited to deionized (DI) water, alcohol (such as ethanol, methanol, isopropanol, etc.) or any combination thereof. For example, the rinsing solution can be formed by equal volumes of water and ethanol. The rinsing of processing frame 114 can be performed under stirring, for example, so that any remaining lignin and hemicellulose matrix collapses (collapse), thereby exposing the retained cellulose-based large fibers. Alternatively or additionally, in some embodiments, the plant material includes a support portion that remains attached to the cellulose-based large fiber and does not undergo delignification. In the subsequent drying process of the plant material, due to rooting and self-densification in the support portion, the exposed large fibers can be self-separated.

[0075] Once the rinsing of processing frame 114 has been completed, or if rinsing is not required at decision frame 112, method 100 can proceed to processing frame 116, where the plant material and any exposed large fibers are dried. The drying of processing frame 116 may include any conductive, convection and / or radiant heating process, including but not limited to an air drying process, a vacuum assisted drying process, an oven drying process, a freeze drying process, a critical point drying process, a microwave drying process, or any combination thereof. For example, the air drying process may include allowing the delignified plant material to dry naturally in static or moving air, which may be at any temperature, such as room temperature (e.g., 23° C.) or elevated temperature (e.g., greater than 23° C.). For example, the vacuum assisted drying process may include subjecting the delignified plant material to reduced pressure, e.g., less than 1 bar, in a vacuum chamber or vacuum oven. For example, the oven drying process may include heating the delignified plant material at elevated temperature (e.g., greater than 23° C.) (e.g., 70° C. or higher) using an oven, hot plate, or other conductive, convection or radiant heating device. For example, a freeze drying process may include reducing the temperature of the delignified plant material to below the freezing point of the fluid therein (e.g., below 0°C), then reducing the pressure to allow the frozen fluid therein to sublime (e.g., below a few millibars). For example, a critical point drying process may include immersing the delignified plant material in a fluid (e.g., liquid carbon dioxide), increasing the temperature and pressure of the bamboo segment to above the critical point of the fluid (e.g., 7.39 MPa, 31.1°C for carbon dioxide), and then gradually releasing the pressure to remove the now gaseous fluid. For example, a microwave drying process may include using a microwave oven or other microwave generating device to induce dielectric heating within the delignified plant material by exposing the delignified plant material to electromagnetic radiation having a frequency in the microwave range (e.g., 300 MHz to 300 GHz) (e.g., a frequency of ~915 MHz or ~2.45 GHz).

[0076] In some embodiments, drying can cause any fluid retained in the macrofibers by chemical treatment and / or rinsing to evaporate. In these embodiments, the capillary effect of evaporation can cause the microfibers of each macrofiber to be pulled together, thereby causing self-densification of the macrofibers. For example, drying can reduce the volume of each cellulose-based macrofiber by at least 10%. After drying at processing frame 116, the moisture content of each macrofiber is less than or equal to 10 wt% (e.g., ≤ 5 wt%). In some embodiments, the density of the dried macrofibers is at least 0.8 g / cm 3 (e.g., ≥1 g / cm 3 ).

[0077] In some embodiments, the delignified cellulose-based large fibers extracted from natural plant materials by the above-mentioned part of method 100 may have a length of at least 5 cm (e.g., 5-200 cm, including 5 cm and 200 cm), a diameter (e.g., the maximum cross-sectional dimension in a plane perpendicular to the length direction) of at least 5 μm (e.g., 5 μm-1 mm, including 5 μm and 1 mm and / or at least 100 μm), or any combination thereof. The delignified cellulose-based large fibers extracted from natural plant materials by the above-mentioned part of method 100 also have enhanced mechanical properties. For example, the delignified cellulose-based large fibers have a mechanical strength of at least 0.5 GPa·cm 3 / g (for example, ≥1GPa·cm 3 / g), a specific strength of at least 40% (e.g., ≥50%), a crystallinity of at least 0.5 GPa (e.g., ≥1 GPa), a Young's modulus of at least 20 GPa (e.g., ≥40 GPa or ≥60 GPa), or any combination thereof.

[0078] 1, the method 100 can proceed from the processing block 116 to the decision block 118, where it is determined whether the delignified cellulose macrofibers should be modified one or more times. For example, when the plant material includes a support portion, the longitudinal ends of each macrofiber remain coupled to the support portion, and the method 100 can proceed from the decision block 118 to the processing block 122, where the macrofibers are severed from the support portion (e.g., by cutting).

[0079] Alternatively or additionally, the delignified cellulosic macrofibers may be modified by introducing one or more functional materials at processing block 120. In some embodiments, the functional materials may be introduced into the internal microstructure or nanostructure of the macrofibers and / or the functional materials may be coated on the outer surface of the macrofibers. For example, the functional materials may include, but are not limited to, conductive materials (e.g., carbon nanotubes, graphene, polypyrrole (PPy), polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT), silver nanoparticles or nanowires, silver, copper, indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), etc.), magnetic materials (e.g., AlNi(Co), FeCr(Co), FeCrMo, FeAlC, FeCrCo, PtC, etc.), piezoelectric materials (e.g., BaTiO3 (BT), lead zirconate titanate (PZT), lead-barium metaniobate (PBLN), quartz, polyvinylidene fluoride (PVDF), etc.), stimulus responsive materials (e.g., ceramic matrix composites (CMC), polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyurethane (PU), epoxy resin), catalytic materials (ZnO, TiO2, Fe2O3, SnO2, Co3O4, LaFeO3, LaCoO3, etc.), or any combination of the foregoing. In some embodiments, modification of processing frame 120 may include, but is not limited to, spin coating, in-situ growth, sol-gel coating, dip coating, spray coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), evaporative coating, sputter coating, immersion growth, or any combination of the foregoing.

[0080] After the cutting of processing box 122 and the modification of processing box 120, or if modification is not required at decision box 118, method 100 can proceed to decision box 124, where it is determined whether the large fibers should be combined with other materials to form a composite material. In some embodiments, the large fibers can be infiltrated and / or coated with a polymer at processing box 126 to form a composite structure. Alternatively or additionally, at processing box 128, the large fibers can be embedded or encapsulated in a matrix or substrate to form a composite structure. In some embodiments, the substrate of the composite structure can be a polymer or concrete, and the embedded large fibers can provide reinforcement for the substrate. After processing box 126, processing box 128, or both, the large fiber content in the composite structure can be at least 0.1wt% (e.g., 0.5wt% to ~80wt%).

[0081] For example, the polymer used for the composite structure (e.g., process block 126 or process block 128) can be epoxy, polyvinyl alcohol (PVA), polyethylene glycol (PEO), polyamide (PA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polyisophthalamide (PMIA), polyisophthalamide (PPTA), polyurethane (PTA), polyisophthalamide (PPTA), polyisophthalamide (PPTA), polyisophthalamide (PPTA), polyisophthalamide (PPA ...PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polyisophthalamide (PMIA), polyisophthalamide (PPTA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PET), polybutylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polyisophthalamide (PMIA), polyp-phenylene terephthalamide (PPTA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PPA), polyisophthalamide (PP Polyester (PU), polycarbonate (PC), polypropylene (PP), high-density polyethylene (HDPE), polystyrene (PS), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene terephthalate adipate (PBAT), poly(butylene succinate-co-adipate) (PBSA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(glycolic acid) (PGA), polypyrrole (PPy ), polythiophene (PTh), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene-vinyl alcohol (EVOH), poly(vinylidene chloride) (PVDC), poly(m-xylylene adipamide) (MXD6), polyethylene (PE), polyvinyl chloride (PVC), poly(methyl methacrylate) (PMMA), acrylonitrile-butadiene-styrene (ABS), polyimide (PI), polyethyleneimine (PEI), polylactic acid (PLA), octadecyltrichlorosilane (OTS), polyoctahedral silsesquioxane (POSS), p-methylstyrene (PMS), polydimethylsiloxane (PDMS), polyethylene naphthalate (PEN), a graft copolymer of acrylonitrile-butadiene-styrene-methyl methacrylate (ABSM), dodecyltrimethoxysilane (DTMS), rosin, chitin, chitosan, protain, vegetable oil, lignin, hemicellulose, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination of the foregoing. For example, the concrete used in the composite structure (eg, process block 128) may be Portland cement, Agro-concrete, MgCO3, Mg(OH)2, or any combination thereof.

[0082] After infiltration of processing box 126 and embedding of processing box 128, or if composite material formation is not required at judgment box 124, method 100 can continue to processing box 130, where the large fibers (or composite structures containing large fibers) can be used. For example, in some embodiments, the delignified large fibers can be used as independent structural components, such as ropes, cables, humidity-activated actuators or springs, woven fabrics, etc. Alternatively or additionally, in some embodiments, large fiber reinforced composites can be used as structural materials, for example, in building construction, packaging, transportation vehicles (e.g., automobiles, trains, aerospace), electronic housings, robots, etc. The delignified large fibers manufactured according to the disclosed technology can also be used in other applications besides the specifically listed applications. In fact, it will be readily understood by those of ordinary skill in the art that the delignified large fibers disclosed herein can be suitable for other applications based on the teachings of the present disclosure.

[0083] Although the frames 102-130 of method 100 have been described as being performed once, in some embodiments, before the next judgment frame or processing frame is performed, multiple repetitions of a specific processing frame may be adopted. For example, the washing of processing frame 108 and / or processing frame 114 may be performed more than once, providing a new washing solution for each iteration. In addition, although the frames 102-130 of method 100 have been shown and described separately, in some embodiments, the processing frames may be combined and performed together (simultaneously or sequentially). In addition, although Fig. 1 shows a specific order of frames 102-130, the embodiments of the disclosed subject matter are not limited thereto. In fact, in some embodiments, these frames may occur in a different order than shown, or may occur simultaneously with other frames.

[0084] Examples of large fiber structures and composite materials

[0085] 2A-2D show various configurations of delignified cellulose macrofibers extracted from natural plant materials. In some embodiments, as shown in FIG. 2A , a single macrofiber 200 may be provided for use. As described above, the macrofiber 200 may have a length L of at least 5 cm (e.g., extending along the longitudinal growth direction of the original plant material) and a diameter d of at least 5 μm (e.g., 5 μm to 1 mm (including 5 μm and 1 mm) and / or at least 100 μm). Alternatively, in some embodiments, a plurality of macrofibers 200 may be combined together to form a structure. For example, as shown in FIG. 2B , a plurality of macrofibers 200 may be arranged in parallel to form a bundle array 202. In this configuration, the macrofibers of the array 202 may be coupled together artificially (e.g., using glue or epoxy resin) or naturally (e.g., due to hydrogen bonding between the facing surfaces of the macrofibers 200). Alternatively, the macrofibers 200 of the array 202 may be entangled with each other, for example, to form a rope or cable.

[0086] In some embodiments, multiple large fibers 200 can be arranged in an array. For example, as shown in FIG. 2C, the large fibers 200 can be arranged to form a regular one-dimensional (1-D) array 204. The array 204 can have equal spacing between adjacent large fibers in a direction perpendicular to the length direction of the large fibers. Alternatively or additionally, as shown in FIG. 2D, the large fibers 200 can be arranged to form a regular two-dimensional (2-D) array 206. The array 206 can have equal spacing between adjacent large fibers in a first direction parallel to the length direction of some large fibers, and can have equal spacing between adjacent large fibers in a second direction perpendicular to the first direction. The spacing in the first direction can be the same or different from the spacing in the second direction. In some embodiments, the large fibers 200 of the array 206 can be, for example, woven or interwoven to form a fabric. Alternatively or additionally, the large fibers can be arranged to form a regular 3-D array, for example, by covering multiple 2-D arrays 206 and / or by providing another 2-D array in which the large fibers extend in a third direction perpendicular to the plane of the 2-D array 206.

[0087] In some embodiments, a 1-D, 2-D, or 3-D array of large fibers can be combined with a substrate to form a composite structure. For example, in FIG. 3A, a batch 310 of delignified large fibers 300 can be arranged in a linear array 314 by process 312. Then, the linear array 314 can be embedded in a substrate 318 or coated by a substrate 318 by process 316 to form a composite structure 320. In another example, as shown in FIG. 3B, a batch 310 of delignified large fibers can be arranged in a biaxial braid pattern 324 by process 312. Then, the biaxial braid 324 can be embedded in a substrate 318 or coated by a substrate 318 by process 316 to form a composite structure 330. In yet another example, as shown in FIG. 3C, a batch 310 of delignified large fibers 300 can be arranged in a triaxial braid pattern 334 by process 312. Then, the triaxial braid 334 can be embedded in a substrate 318 or coated by a substrate 318 by process 316 to form a composite structure 340. 3D, the batch 310 of delignified macrofibers 300 can be arranged in a knitted braid pattern 344 by process 312. The knitted braid 344 can then be embedded in or coated by a substrate 318 by process 316 to form a composite structure 350.

[0088] Other arrangements and configurations of macrofibers in a composite material are also possible according to one or more contemplated embodiments. For example, the macrofibers in a composite material may have a random arrangement (e.g., no discernible order or arrangement), an irregular pattern (e.g., the spacing between adjacent macrofibers varies throughout the array), a pattern without spacing (e.g., the opposing surfaces of adjacent macrofibers are in direct contact with each other), or any other type of pattern or arrangement.

[0089] As described above, the polymer used for the substrate 318 in any of Figures 3A-3D can be epoxy, PVA, PEO, PA, PET, PBT, PTT, PAN, PA6, PMIA, PPTA, PU, ​​PC, PP, HDPE, PS, PCL, PBS, PBAT, PBSA, PHB, PHBV, PGA, PPy, PTh, PVDF, PVF, EVOH, PVDC, MXD6, PE, PVC, PMMA, ABS, PI, PEI, PLA, OTS, POSS, PMS, PDMS, PEN, ABSM, DTMS, rosin, chitin, chitosan, protain, vegetable oil, lignin, hemicellulose, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination thereof. Alternatively, the substrate 318 in any of Figures 3A-3D can be concrete, such as Portland cement, agricultural concrete, MgCO3 and Mg(OH)2.

[0090] In some embodiments, in order to form a composite structure, large fibers arranged in an appropriate pattern can be placed in a mold, and a substrate in a substantially fluid state can be poured into the mold. After solidification, the substrate can adopt a substantially immobile state (e.g., a solid is set), wherein the large fibers are retained. In some embodiments, solidification can be performed by applying pressure, heat, or both to the mold. Alternatively or additionally, in some embodiments, the substrate can be infiltrated into and / or around the large fibers by applying a vacuum. For example, FIG. 4A shows an exemplary device 400 for vacuum infiltration of a substrate 414 (e.g., a polymer) into an arrangement 410 of delignified large fibers to form a composite material 418. The vacuum infiltration device 400 may include a housing 402 having an inlet port 404 for inflow of a polymer (or a polymer precursor) and a vacuum port 406 for applying a vacuum. In some embodiments, the device 400 may also include a conforming vacuum chamber 408 (e.g., a vacuum bag) that collapses when a vacuum is applied to the port 404. The collapsed vacuum chamber 408 can reduce or eliminate the external volume around the delignified macrofiber arrangement 410, thereby ensuring that the polymer 414, when flowing in at 412, primarily penetrates the macrofibers 410 (e.g., instead of embedding the macrofibers in the polymer, or at least reduces the distance between the outer surface of the polymer and the macrofibers embedded therein). Once the composite material 418 is formed in the final stage 416, the vacuum can be released and the composite material can be removed for further curing or use.

[0091] FIG. 4B shows another exemplary device 420 for performing vacuum infiltration of a substrate (e.g., a resin or other polymer) into delignified large fibers. For example, multiple layers 426 of delignified cellulose large fibers (e.g., each layer is formed as a woven fabric or mat) can be placed in a single-sided smooth mold 430. The stacked large fiber layer 426 can be covered by a thin spacer film (e.g., nylon), encapsulated in a vacuum bag 428 (e.g., polyethylene), and tightly sealed. Then, the resin can be introduced from a source 432 into the mold 430 by applying vacuum pressure from a vacuum pump 422. The resin trap 424 between the vacuum pump 422 and the mold 430 can prevent the resin from accidentally entering and damaging the vacuum pump 422 during operation. The resin injected by the vacuum pressure impregnates and completely penetrates the cellulose large fiber stack to form a composite structure, after which the composite material can be moved out to a hot press for final curing of the resin, for example, at a pressure of 13 MPa and a temperature of 150°C.

[0092] Fabrication Examples and Experimental Results

[0093] Extracted bamboo fiber

[0094] Can be by using one or more chemical treatments to carry out delignification and extract cellulose macrofiber from the block of natural bamboo.Fig. 5 A shows the partial cross-sectional view of the bamboo segment 500 that is in its natural state of occurrence.Segment 500 has the culm wall 502 around the hollow inner region 516, and the hollow inner region 516 is divided into the inner node region 512 along the length of culm wall 502 by the node 08 formed by the inner node diaphragm 510.Culm wall 502 has the fiber extending along the longitudinal direction 528 (for example, bamboo growth direction or the direction of the axis limited by the hollow inner region 516) of bamboo segment 500, and it embeds lignin matrix.One or more bifurcated branches (branch stub) 514 can extend from specific inner node region 512 and can be used as the culm wall of new bamboo segment possibly from the root of its growth (for example, thus for new bamboo segment to limit different longitudinal directions).

[0095] In the culm wall 502, bamboo shows a hierarchical cell structure, which has porous cells providing nutrient transport and dense cells providing mechanical support. For example, Fig. 5B-5D shows a cross-sectional image of a bamboo segment 500, particularly, showing the microstructure of thin-walled cells 522, ducts 524 and fiber bundles or large fibers 526 constituting the culm wall 502. Large fibers 526 are highly aligned and extend substantially parallel to the longitudinal direction 528, while thin-walled cells 522 can be parallel or perpendicular to the longitudinal direction 528. These large fibers 526 are characterized in having thick cell walls, which are assembled by aligned semi-crystalline lignocellulose microfibers (e.g., 528 in the detailed view 616 of Fig. 6 A). For example, the average diameter of microfibers is ~12 μm, and aspect ratio is 150~200. These microfibers are composed of closely packed cellulose nanofibers (e.g., 530 in the detailed view 616 of Fig. 6 A). The cellulose nanofibers have repeating cellulose polymer chains 532 arranged in alternating amorphous and highly ordered (eg, crystalline) regions, forming the basic structural element of the bamboo cellulose macrofibers 526 .

[0096] During the growth of bamboo, a large amount of lignin is biosynthesized and deposited in the cell corner area between solid large fiber 526 and porous thin-walled cells 522, forming a tightly bound interface through a large number of covalent bonds and hydrogen bonds. Therefore, the rigid large fiber 526 of bamboo (e.g., with an elastic modulus of ~25.6GPa) is embedded in the matrix of hollow thin-walled cells 522 (e.g., elastic modulus of ~3.7GPa), and the large fiber 526 and cells 522 are bonded together by a natural polymer matrix composed of lignin and hemicellulose. This structure makes it difficult to physically separate the large fibers from bamboo without damaging them and producing obvious defects. This damage / defect leads to a relatively low tensile strength, for example, ~300MPa.

[0097] Fig. 6A shows complete bamboo macrofibers extracted by delignification. Before delignification, natural bamboo 600 shows a cell hierarchy of macroscale vessels 524, mesoscale thin-walled cells and microscale microfibers 528 in macroscale fiber bundles 526. The lignin-hemicellulose matrix 602 connecting microfibers 528 to thin-walled cells can be dissolved or decomposed by delignification 604, thereby releasing complete cellulose macrofibers 526. In the extraction process, formic acid peroxide is used as a gentle delignification treatment, selectively decomposing lignin / hemicellulose adhesive 602 and thin-walled thin-walled cells, thereby making almost solid cellulose macrocellulose separated when there is almost no mechanical damage. However, as mentioned above, other chemicals can be used for delignification. In particular, in the delignification process, formic acid peroxide selectively reacts with hydrophobic lignin and dissolves hydrophobic lignin, causing thin-walled cells to decompose and naturally separate from cellulose macrofibers 608 (for example, after the bamboo stems treated in water are briefly washed). After treatment, the natural structure of the delignified cellulose macrofibers 608 is well preserved, as shown in 606, while the selectively delignified thin-walled cells are removed in a subsequent washing step, enabling the rapid separation of thousands of high-strength cellulose macrofibers 608 from a single bamboo stem.

[0098] After delignification, the extracted delignified macrofibers can be air dried 610, whereby the capillary forces generated by the evaporation of water collapse the constituent cellulose microfibers 528 and their nanofibers together. This collapse results in a dense cellulose macrofiber structure with a reduced size. For example, by simple air drying, denser macrofibers can be extracted while reducing structural defects, increasing crystallinity (from 42% to 65%) and nanofiber alignment index (from 0.91 to 0.93). The resulting macrofibers exhibit a tensile strength of up to 2.2 GPa and a Young's modulus of up to 120 GPa. The crystallinity and orientation of the cellulose nanofibers within the macrofibers contribute to the longitudinal stiffness and strength of the macrofibers.

[0099] In the example of the fabrication, a bamboo stem with a height of 17 cm, a diameter of 5.8 cm, and a wall thickness of 0.9 cm was immersed in a formic acid peroxide solution and heated at a mild temperature of 50°C for 12 hours. As shown in FIG6B , a portion 618 of the bamboo stem was retained outside the formic acid peroxide solution to serve as a support for a portion 620 of the bamboo stem immersed in the solution. The solution quickly diffused through the bamboo cavities and pits to the entire material, causing the hydroxyl radicals (HO·) and superoxide anions (O2·) generated by the formic acid peroxide to form a hygroscopic substance. -) free radicals attack the electron-rich aromatic rings and olefin side chain structures of lignin, resulting in side chain oxidation, ring cracking, and degradation of lignin and hydrolysis of hemicellulose to monosaccharides. During the chemical delignification process, the natural yellow color of bamboo stems gradually weakens and eventually becomes completely white (as shown in Figure 6C), which indicates that most of the colored lignin and hemicellulose have been removed from the cell wall. After the delignification process, the bamboo stems are transferred to a 0.5wt% sodium hydroxide solution to remove residual lignin and hemicellulose components, and then washed several times with deionized water to rinse off any residual chemicals in the treated bamboo. After processing and washing, the delignified bamboo stems 622 are clearly separated into thousands of different macroscopic scale fibers, as shown in Figures 6D-6E.

[0100] The microstructural changes of bamboo stems during chemical delignification were studied using scanning electron microscopy (SEM). In natural bamboo 600, solid macrofibers 526 characterized by thick walls are embedded in a matrix of hollow honeycomb-like parenchyma cells 522 with thin walls, as shown in Figures 6F-6G. However, after 10 hours of delignification treatment, the parenchyma cells 522 gradually began to separate from the macrofibers 526, as shown in Figure 6H, while the ordered structure of aligned microfibrils in the macrofibers 526 remained unchanged, as shown in Figure 6I. After treatment, the rigid macrofibers 526 remained intact and aligned along the longitudinal fiber axis, while the parenchyma cells 522 were significantly removed due to the loss of the connective lignin matrix. In particular, hydroxyl groups (HO·) and superoxide anions (O2· - ) The high selectivity and efficiency of the free radicals decompose the thin-walled cells 522 and the binder into water-soluble lignin and hemicellulose molecular fragments, which can be easily removed by washing. In contrast, the large fibers 526 better retain their natural structure due to their low lignin content. Therefore, the thin-walled cells 522 can be easily removed while causing minimal damage to the large fibers 526.

[0101] After the delignification process is complete, subsequent air drying of the separated macrofibers creates capillary tension that causes the constituent cellulose nanofibers to collapse together. As a result, the cellulose macrofibers 614 exhibit a volume shrinkage of approximately 10-12% in the cross-section of the cellulose macrofibers, resulting in a denser structure that promotes a higher number of hydrogen bonds and greater van der Waals interactions. It should also be noted that the delignified cellulose macrofibers retain their highly ordered structure after drying, in which the tightly packed cellulose nanofibers are aligned in the longitudinal direction without obvious defects or separation. In addition, by adjusting the reaction conditions, multiple bamboo stems can be processed simultaneously to isolate cellulose macrofibers of desired lengths for various applications.

[0102] In another example of manufacturing, 5-year-old bamboo (Phyllostachys chinensis) with a stem height of 17 cm, a diameter of 5.8 cm and a wall thickness of 0.9 cm was delignified. The raw bamboo stalks were cut into individual stems (without nodes) of different lengths and boiled in water for 1 hour to remove water-soluble organic matter and any residual air. The bamboo stems were then delignified using a 10v / v% peroxyformic acid solution (synthesized from a mixture of 30% hydrogen peroxide and formic acid in a molar ratio of 1:1, and 1wt% sulfuric acid was added as a catalyst). The bamboo stems were soaked in peroxyformic acid for 12 hours at 50°C, and then the bamboo stems were neutralized with a 0.5wt% sodium hydroxide solution for 5-10 minutes. The bamboo stems were subsequently washed with deionized water several times to remove chemicals and separate the thin-walled cells from the cellulose macrofibers. The treated bamboo was then dried at room temperature for 24-48 hours until the moisture content was less than 5wt%.

[0103] Under polarized light, the resulting delignified cellulose macrofibers extracted from bamboo showed bright birefringence, as shown in Figures 7A-7B, indicating the uniform removal of amorphous hemicellulose and lignin and the alignment and crystallinity of the cellulose microfibrils. This suggests that the cellulose molecular chains that make up these macrofibers are also ordered. For comparison, a mechanical extraction method (i.e., without delignification treatment) was used to separate lignocellulosic macrofibers from bamboo stems. Unlike chemically separated macrofibers, the mechanically extracted macrofibers showed a dark surface under polarized light due to the presence of amorphous lignin and hemicellulose, as shown in Figures 7C-7D. Delignified cellulose macrofibers are also denser than mechanically extracted macrofibers, for example, the density of delignified macrofibers is 1.45 g / cm 3 , while the density of mechanically extracted large fibers is 1.12 g / cm 3 The density of natural bamboo stem is 0.75g / cm 3 Delignified cellulose macrofibers are also characterized by a reduction in the interlamellar spacing between cellulose crystalline layers (e.g. This change may result in enhanced interactions between cellulose fibrils and molecular chains of bamboo cellulose macrofibers (e.g., hydrogen bonding, van der Waals forces) and may be caused by the removal of amorphous lignin and hemicellulose and evaporation-driven shrinkage during air drying.

[0104] To compare the alignment of cellulose nanofibers in the two macrofiber samples, their orientation index (f c). The alignment index ranges from 0 to 1, with unity corresponding to perfect alignment. The nanofiber orientation index of delignified cellulose macrofibers increased to 0.93, compared to 0.91 for mechanically extracted macrofibers. This suggests that the alignment of the cellulose Iβ crystalline nanostructures is improved after the delignification and drying process. The improvement in alignment may be due to the large reduction in amorphous lignin and hemicellulose, as well as the self-alignment of highly crystalline cellulose nanofibers that occurs during the slow drying step, which results in a significant volume shrinkage (~12%) of the bamboo cellulose macrofibers.

[0105] The crystallinity index of the material was also calculated based on the ratio of the integrated fitted intensity of amorphous and crystalline cellulose in the 2D-WAXS results. Delignified cellulose macrofibers exhibited a higher crystallinity index (64.9%) compared to mechanically extracted macrofibers (42.4%). Small angle X-ray scattering (SAXS) was used to characterize the molecular alignment of the cellulose chains that make up the nanofibers. Compared to mechanically extracted macrofibers, which showed a diamond pattern with stripes perpendicular to the equatorial and meridian stripes, SAXS analysis of delignified cellulose macrofibers showed a stronger equatorial stripe scattering pattern, indicating well-aligned crystalline cellulose along and throughout the fiber axis. This tightly packed, highly aligned and highly crystalline cellulose structure can achieve high-strength macrofibers.

[0106] The tensile mechanical properties of delignified cellulose macrofibers were characterized according to the ASTM D3379-75 standard test method. Tensile tests of 20 delignified cellulose macrofibers with a gauge length of 2-cm showed similar stress-strain curves, demonstrating the consistency of the material. The stress-strain behavior under load was approximately linear elastic before reaching the breaking stress, with an average tensile strength of 1.90±0.32GPa and a Young's modulus of 91.3±29.7GPa, as shown in Figures 8A-8B. As shown in Figure 8B, these values ​​of tensile strength and Young's modulus are 7.2 times and 6.2 times those of natural bamboo stem raw materials, respectively. In addition, the tensile strain of delignified cellulose macrofibers was 2.67% (~2 times higher than natural bamboo stems). When combined with the high tensile strength, this results in a tensile strength of 29.9MJ m -3 The high work of fracture of the delignified cellulose macrofibers is 3 to 12 times higher than that of bamboo stems and mechanically extracted macrofibers. Considering the cross-sectional area or length, the ultimate tensile strength of delignified cellulose macrofibers of different diameters ranges from 1.48 GPa to 2.22 GPa, as shown in Figure 8D, while the Young's modulus ranges from 60 GPa to 120 GPa. Delignified cellulose macrofibers with smaller diameters and shorter lengths tend to have higher strengths than those with larger diameters.

[0107] The mechanically extracted large fiber control shows significantly poor mechanical properties, with a tensile strength of 560 ± 200 MPa and a Young's modulus of 49.3 ± 5.6 GPa, as shown in Figures 8A-8B. One of the factors that may lead to poor mechanical properties may be the internal damage (e.g., microcracks of fibrils) produced during mechanical defibrillation. In addition, since the Young's modulus of crystalline cellulose (e.g., 110-220 GPa) is much higher than amorphous lignin and hemicellulose (e.g., 6 GPa and 8 GPa), the different composition structures of the mechanically extracted large fibers also lead to poor mechanical properties compared to delignified cellulose large fibers.

[0108] After the tensile test, the good alignment of cellulose nanofibers in bamboo cellulose macrofibers can also be observed from the fracture surface, confirming the reinforcement mechanism of the tightly laminated cellulose nanofibers through the enhanced bonding interface. In contrast, the nanofibers in the control mechanically extracted macrofibers are still covered with lignin and hemicellulose, which will interfere with the interfacial bonding between the constituent nanofibers. Therefore, the compact delignified cellulose macrofibers are composed of dense and highly aligned cellulose nanofibers with a high crystallinity of ∼65% and a small microfiber angle of 7.2°, showing mechanical properties far superior to those of the mechanically extracted macrofibers, which have a low crystallinity of ∼42% and a larger microfiber angle of 9.3°.

[0109] In another example of manufacturing, natural bamboo stalks with a length of 170 mm, a diameter of 60 mm, and a cell wall thickness of 8 mm were immersed in a boiling solution of NaOH (10 wt%) and Na2SO3 (5 wt%) at 70°C for 4 hours to partially (but not completely) remove lignin and hemicellulose. Subsequently, the chemically treated bamboo stalks were washed with deionized water to remove chemicals and other impurities. The partially delignified bamboo stalks were then placed in a solution of hydrogen peroxide (10 wt%) and acetic acid (10 w%) at 60°C for 4 hours. Finally, delignified bamboo fibers were separated from thin-walled cells by stirring in the solution and then drying in air.

[0110] Composite materials formed using extracted bamboo fibers

[0111] Delignified bamboo fiber reinforced polymer composites with improved mechanical properties were manufactured by combining chemical treatment and mechanical pressing. For example, 48-month-old bamboo stalks with an internode length of 30 cm were heated in a solution containing sodium sulfite NaOH (2.5 mol L -1 ) and Na2SO3 (0.4 mol L -1) for 6 hours to partially dissolve lignin and hemicellulose. The partially delignified bamboo stalks were then immersed in deionized water to remove any residual chemicals. Subsequently, the partially delignified bamboo stalks were immersed in a solution of hydrogen peroxide and acetic acid for 2 hours to further remove lignin and hemicellulose. Finally, the delignified bamboo fibers were immersed in a PLA solution under vacuum. The assembled delignified bamboo fibers were used to manufacture composites by compression molding technology in a hot press mold along the particle direction at 50°C and a pressure of 5.0MPa for 24 hours.

[0112] In another example of fabrication, 48-month-old bamboo culms with an internode length of 30 cm were placed in a humidified water bath containing NaOH (2.5 mol L -1 ) and Na2SO3 (0.4 mol L -1 ) for 6 hours to partially dissolve the lignin and hemicellulose. The partially delignified bamboo stalks were then immersed in deionized water to remove any residual chemicals. Subsequently, the partially delignified bamboo stalks were immersed in a hydrogen peroxide and acetic acid solution for 2 hours to further remove the lignin and hemicellulose. Finally, the delignified bamboo was immersed in an inorganic matrix consisting of ordinary Portland cement under vacuum. The content of white bamboo fiber used for reinforcement was 6% (by mass) relative to the total dry mass content, which was equivalent to about 12% (by volume). The cement-based composite was molded into 160×40mm 2 The sample was then pressed at 3.2 MPa for 5 minutes and the wet sample was sealed in a plastic bag and cured at room temperature for 1 day, and then further cured at (20 ± 1) ° C and relative humidity exceeding 90% until the test stage.

[0113] In another example of manufacturing, delignified cellulose macrofibers are used to manufacture bamboo fiber reinforced polymer composites (BFRC). For example, as shown in FIG9A, 1000 delignified cellulose macrofibers 902 are woven into a twill fabric mat 900. In the fabric mat, the macrofibers are interwoven in an aligned structure in the orthogonal direction without entanglement. The fabric mat is then impregnated with epoxy resin by vacuum-assisted resin transfer molding (e.g., using the apparatus and process described above with respect to FIG4B). Delignified cellulose macrofibers have high surface energy for epoxy resin, thereby enabling high interfacial bonding strength. For example, when a droplet of epoxy resin is directly applied to a single cellulose macrofiber, a contact angle of 38° is observed, indicating that the resin has good wettability. The wettability can be attributed to a large number of hydroxyl groups exposed on the surface of delignified cellulose macrofibers. After the resin injection process, the composite material is further compressed and thermally cured. For example, FIG9B shows a BFRC product 904 consisting of two orthogonally woven (0 / 90) bamboo cellulose macrofibers impregnated in a curing resin. The tensile strength of BFRC 904 in both the horizontal and vertical (X and Y) directions is ˜350±28 MPa, as shown in FIG. 9C .

[0114] Extracted grass fiber

[0115] Natural grass is characterized by having a heterogeneous structure 1004 consisting of hollow vessels 1008 and thin-walled cells 1006 and fibers 1010 extending in the longitudinal growth direction, as shown in Figures 10C-10D. In this structure, the porous vessels 1008 and thin-walled cells 1006 are mainly responsible for transporting water and nutrients, while the cellulose fibers 1010 mainly provide structural support. Inside the plant, these components are bonded together by lignin and hemicellulose to form a complete structure. Although essential to living plants, the porous vessels and thin-walled cells act as defects when used as structural materials, thereby reducing the mechanical properties of natural grass. Therefore, the fibers 1010 can be chemically extracted from natural grass to be used as a separate structural material.

[0116] In a fabricated example, gladiolus leaves 1000 (FIG. 10A) were soaked in water overnight, after which they were delignified by immersing the wet leaves in a boiling solution of NaOH and Na2SO3 for 30 minutes. After washing with deionized water and drying, macro-scale fibers 1002 can be harvested, as shown in FIG10B.

[0117] In another example of manufacturing, gladiolus leaves with a length of 100 cm were used. The long gladiolus leaves were immersed in a boiling solution containing NaOH (10wt%) and Na2SO3 (5wt%) at 70°C for 0.5 hours to partially (but not completely) remove lignin and hemicellulose. Subsequently, the chemically treated gladiolus leaves were washed with deionized water to remove chemicals and other impurities. The partially delignified gladiolus leaves were then immersed in a solution of hydrogen peroxide (5wt%) and acetic acid (2wt%) at 50°C for 1 hour. Chemical treatment can effectively reduce the content of lignin and hemicellulose in large fibers, for example, from 19wt% and 23wt% in natural gladiolus leaves to 2.3wt% and 5.5wt% in delignified large fibers, respectively. The content of cellulose can also be increased, for example, from 45wt% in natural gladiolus leaves to 85wt% in delignified large fibers.

[0118] After delignification, the obtained gladiolus macrofibers were dried in an oven at 50°C. The obtained lignocellulosic macrofibers were ∼1 m long and had a dense structure consisting of regularly stacked and tightly bound cellulose microfibers. On a finer scale, many nanofibers aligned parallel to the fiber axis constituted the microfibers. The lignocellulosic fibers obtained from grass can have excellent mechanical properties, for example, a tensile strength of up to 1170 MPa, which is much higher than the 60 MPa of the original grass. Due to the removal of the hollow vessels and thin-walled cells, as well as amorphous hemicellulose and lignin, the obtained lignocellulosic fibers exhibited a tensile strength of 1.31 g / cm -3 The high density of cellulose microfibrils (e.g., 3.7 times higher than that of natural grass) was observed. Small angle X-ray scattering (SAXS) analysis further indicated a highly ordered alignment of cellulose microfibrils in the lignocellulose macrofibrils. In addition, as shown in FIG10E , the lignocellulose macrofibrils 1012 are characterized by having a smooth surface and a dense structure due to the removal of the hollow vessels 1008 and the thin-walled cells 1006 (e).

[0119] The mechanical properties of the lignocellulosic macrofibers extracted from natural grass were investigated by tensile tests. As shown in Figure 12, the lignocellulosic macrofibers exhibited higher maximum force and similar elongation at break compared to natural grass. The lignocellulosic macrofibers exhibited a tensile strength of 1.07 GPa and a Young's modulus of 89.8 GPa, which were 16 and 18 times that of the original natural grass, respectively. The lignocellulosic macrofibers also exhibited a tensile strength of greater than 0.75 GPa cm 3 / g and a specific strength greater than 60 GPa cm 3 / g specific modulus. In addition, the lignocellulose macrofibers can show a wet strength of 0.51 GPa.

[0120] The aligned microstructure of lignocellulose macrofibrils contributes to the enhanced mechanical properties. In particular, cellulose fibrils are tightly packed and interlocked at both the microscale and nanoscale, which can enhance the interfacial bonding (e.g., van der Waals forces and hydrogen bonds) between them. Once external force is applied, all fibrils are subjected to tensile stress together, which also leads to uniform fracture of the smart cellulose fiber structure. In addition, the dense unidirectional fibers can effectively transmit and disperse stress, thereby achieving the superb mechanical properties of wood fibers.

[0121] In another example of manufacturing, a block of natural grass blades 1102 having a length of 100 cm ( FIG. 11A ) was subjected to different delignification conditions. In FIG. 11B , the grass blades 1102 were only partially delignified, 1104 represents the blades after partial delignification but before rinsing, and 1106 represents the blades after partial delignification and after rinsing. In FIG. 11C , the grass blades 1102 have been fully delignified (e.g., ≥ 90% lignin removed), 1108 represents the blades after full delignification but before rinsing, and 1110 represents the blades after full delignification and after rinsing.

[0122] Composite materials formed using extracted grass fibers

[0123] As mentioned above, the lignocellulosic macrofibers extracted from grass can exhibit relatively strong mechanical properties, which is helpful for making high-strength composites. In the example of the fabrication, the lignocellulosic grass fibers were used as a reinforcing material for making high-performance polymer composites. Specifically, 10 cm grass was heated in a solution containing 2 mol L NaOH. -1 ) and Na2SO3 (0.3 mol L -1 ) for 4 hours to partially dissolve the lignin and hemicellulose therein. The partially delignified grass was then immersed in water to remove any remaining chemicals. Subsequently, the partially delignified grass was immersed in a hydrogen peroxide and acetic acid solution for 1 hour to further remove the lignin and hemicellulose. Finally, the resulting macrofibers were coated with an organic polymer to form a composite material. The macrofiber content in the composite was 10%. The macrofiber reinforced polymer composite was molded into 100×100mm 2 The specimen thickness was about 5 mm in the plate. The specimen was then pressed at 2 MPa for 5 min, and the wet specimen was sealed in a plastic bag to cure at room temperature.

[0124] In another fabricated example, 15 cm of grass was placed in a solution containing NaOH (2.5 mol L -1 ) and Na2SO3(0.35molL -1) for 3 hours to partially dissolve the lignin and hemicellulose therein. The partially delignified grass was then immersed in water to remove any remaining chemicals. Subsequently, the partially delignified grass was immersed in a solution of hydrogen peroxide and acetic acid for 2 hours to further remove the lignin and hemicellulose. Finally, the resulting macrofibers were coated with an organic polymer. The macrofiber content in the composite was 8%. The macrofiber reinforced polymer composite was molded into 100×100mm 2 The thickness of the sample was about 7 mm. The sample was then pressed at 2.5 MPa for 10 min and cured at room temperature.

[0125] Functionalized extracted fibers

[0126] The delignified cellulose macrofibers were modified by dip-coating the polypyrrole solution 10 times at a speed of 3 mm / min. The polypyrrole dip-coated macrofibers were dried at 80° C. for 6 hours to obtain conductive functional macrofibers.

[0127] In another example, delignified cellulose macrofibers were soaked in a ZnO precursor solution for 5 hours. After the treatment, the macrofibers were slowly removed from the solution and allowed to stand at room temperature for 30 minutes. The resulting macrofibers were then dried at 80°C for 6 hours and then slowly cooled. Finally, ZnO particles were grown on the surface of the macrofibers to obtain ZnO-coated macrofibers with photocatalytic function.

[0128] Other Examples of Disclosure Technology

[0129] In view of the above implementation of the disclosed subject matter, the present application discloses additional examples in the clauses listed below. It should be noted that a feature of a separate clause, or multiple features of a combined clause, and optionally, combined with one or more features of one or more other clauses, also belong to other examples within the scope of the disclosure of the present application.

[0130] Item 1. An engineered plant material comprising one or more substantially delignified cellulose-based fibers chemically extracted intact from a matrix of lignin and hemicellulose in a mass of natural plant material.

[0131] Clause 2. A composite material comprising:

[0132] a plurality of substantially delignified cellulose-based fibers, each cellulose-based fiber being chemically extracted intact from a matrix of lignin and hemicellulose in a respective mass of natural plant material; and

[0133] A polymer that permeates each cellulose-based fiber.

[0134] Clause 3. A composite material comprising:

[0135] Structural matrix; and

[0136] A plurality of substantially delignified cellulose-based fibers are disposed within the structural matrix, each cellulose-based fiber being chemically extracted intact from a lignin and hemicellulose matrix in a corresponding mass of natural plant material.

[0137] Clause 4. A material as described in any clause or example herein, in particular clause 3, wherein the structural matrix comprises a polymer or concrete.

[0138] Clause 5. The material described in any clause or example herein, in particular any of clauses 2 and 4, wherein the polymer comprises epoxy resin, polyvinyl alcohol (PVA), polyethylene glycol (PEO), polyamide (PA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polymethylene isophthalamide (PMIA), polyp-phenylene terephthalamide (PPTA), polyurethane (PU), polycarbonate (PC), polypropylene (PP), high-density polyethylene (HDPE), polystyrene (PS), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene terephthalate adipate (PBAT), poly(succinic acid-co-adipate) (PBSA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(glycolic acid) (PG A), polypyrrole (PPy), polythiophene (PTh), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene vinyl alcohol (EVOH), poly(vinylidene chloride) (PVDC), poly(m-xylylene adipamide) (MXD6), polyethylene (PE), polyvinyl chloride (PVC), poly(methyl methacrylate) (PMMA), acrylonitrile-butadiene-styrene (ABS), polyimide (PI), polyethyleneimine (PEI), polylactic acid (PLA), octadecyltrichlorosilane (OTS), polyoctahedral silsesquioxane (POSS), p-methylstyrene (PMS), polydimethylsiloxane (PDMS), polyethylene naphthalate (PEN), a graft copolymer of acrylonitrile-butadiene-styrene-methyl methacrylate (ABSM), dodecyltrimethoxysilane (DTMS), rosin, chitin, chitosan, protain, vegetable oil, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination thereof.

[0139] Clause 6. The material described in any clause or example herein, in particular any of clauses 4-5, wherein the concrete comprises Portland cement, agricultural concrete, magnesium carbonate (MgCO3), magnesium hydroxide (Mg(OH)2), or any combination thereof.

[0140] Clause 7. A material as described in any clause or example herein, in particular any one of clauses 2 to 6, wherein the content of the plurality of cellulose-based fibers in the composite material is at least 0.1 wt%.

[0141] Clause 8. A material as described in any clause or example herein, in particular any of clauses 1 to 7, wherein the natural plant material is a species of the order Poaceae.

[0142] Clause 9. A material as described in any clause or example herein, in particular any one of clauses 1 to 8, wherein the natural plant material is a species in the family Poaceae.

[0143] Clause 10. A material as described in any clause or example herein, in particular any of clauses 1 to 9, wherein the natural plant material is natural grass.

[0144] Clause 11. The material described in any clause or example herein, in particular any of clauses 1 to 10, wherein the natural plant material comprises bamboo, reed, sugar cane, corn, wheat, rice, jute, hemp, kenaf, ramie, banana, corn, wheat, rice, roselle, rattan, sorghum, sisal, palm, henequen, abaca, pineapple, curaua, yucca, cabuya, pandanus, abaca, gladiolus or agave.

[0145] Clause 12. A material as described in any clause or example herein, in particular any of clauses 1 to 11, wherein each cellulose-based fiber has a length of at least 5 cm and / or a maximum cross-sectional dimension in a plane perpendicular to the length direction of at least 5 μm.

[0146] Clause 13. A material as described in any clause or example herein, in particular any one of clauses 1 to 12, wherein the length of each cellulose-based fiber is between 5 cm and 200 cm, inclusive.

[0147] Clause 14. The material of any clause or example herein, in particular any one of clauses 1 to 13, wherein the maximum cross-sectional dimension (also referred to herein as diameter) of each cellulose-based fiber is between 5 μm and 1 mm, inclusive.

[0148] Clause 15. A material as described in any clause or example herein, in particular any one of clauses 1 to 14, wherein the maximum cross-sectional dimension of each cellulose-based fiber is at least 100 μm.

[0149] Clause 16. A material as described in any clause or example herein, in particular any one of clauses 1 to 15, wherein each cellulose-based fiber has a strength of at least 0.5 GPa·cm 3 / g (for example, ≥1GPa·cm 3 / g) specific strength, at least 40% (e.g., ≥50%) crystallinity, at least 0.5 GPa (e.g., ≥1 GPa) tensile strength, at least 20 GPa (e.g., ≥30 GPa or ≥60 GPa) Young's modulus, at least 0.8 g / cm 3 (e.g., ≥1 g / cm 3 ), or any combination of the foregoing.

[0150] Item 17. The material described in any item or example herein, in particular any item of items 1-16, wherein each cellulose-based fiber has a cellulose content of at least 70 wt% (e.g., ≥85 wt%), a hemicellulose content of less than or equal to 10 wt% (e.g., ≤6 wt%), a lignin content of less than or equal to 10 wt% (e.g., ≤4 wt%), or any combination of the foregoing.

[0151] Clause 18. The material of any clause or example herein, in particular any one of clauses 1 to 17, wherein each cellulose-based fiber has a moisture content less than or equal to 10 wt% (eg, ≤5 wt%).

[0152] Clause 19. The material described in any clause or example herein, in particular any of clauses 1-18, further comprising a conductive additive, a magnetic additive, a piezoelectric material, a stimulus-responsive material, a catalytic material, or any combination thereof provided on or within each cellulose-based fiber.

[0153] Clause 20. A method comprising:

[0154] (a) subjecting a piece of natural plant material to one or more chemical treatments to remove substantially all lignin therefrom; and

[0155] (b) after (a), extracting a plurality of substantially delignified cellulose-based fibers separated from each other from the chemically treated mass.

[0156] Clause 21. The method of any clause or example herein, in particular clause 20, wherein (b) comprises stirring the chemically treated mass in the solution.

[0157] Clause 22. The method of any clause or example herein, in particular any of clauses 20-21, wherein at least one of the one or more chemical treatments comprises partial or complete immersion in one or more chemical solutions.

[0158] Clause 23. The method of any clause or example herein, in particular any of clauses 20-22, wherein the one or more chemical solutions comprise an alkaline solution.

[0159] Clause 24. The method of any clause or example herein, in particular any of clauses 22-23, wherein the one or more chemical solutions include sodium hydroxide (NaOH), lithium hydroxide (LiOH), potassium hydroxide (KOH), sodium sulfite (Na2SO3), sodium sulfide (Na2S), Na n S (where n is an integer), urea (CH4N2O), sodium bisulfite (NaHSO3), sulfur dioxide (SO2), anthraquinone (C 14 H8O2), methanol (CH3OH), ethanol (C2H5OH), butanol (C4H9OH), formic acid (CH2O2), hydrogen peroxide (H2O2), acetic acid (CH3COOH), butyric acid (C4H8O2), formic acid peroxide (CH2O3), acetic acid peroxide (C2H4O3), ammonia (NH3), p-toluenesulfonic acid (p-TsOH), sodium hypochlorite (NaClO), sodium chlorite (NaClO2), chlorine dioxide (ClO2), chlorine (Cl2), or any combination of the foregoing.

[0160] Clause 25. The method of any clause or example herein, in particular any one of clauses 20-24, wherein after (b), the plurality of cellulose-based fibers remain attached to the base of the natural plant material, and the method further comprises severing the cellulose-based fibers from the base.

[0161] Clause 26. The method described in any clause or example herein, in particular any of clauses 20-25, further comprising:

[0162] (c) After (b), drying the cellulose-based fibers to evaporate water from each cellulose-based fiber resulting in densification thereof.

[0163] Item 27. The method of any item or example herein, in particular item 26, wherein the drying of (c) comprises exposure to air or gas flow, exposure to a stagnant volume of air or gas, exposure to a vacuum, exposure to room temperature, heating to a temperature above room temperature, or any combination thereof.

[0164] Clause 28. The method of any clause or example herein, in particular any of clauses 26-27, wherein, after (c), each cellulose-based fiber has a moisture content of 10 wt% or less (eg, ≤ 5 wt%).

[0165] Clause 29. The method of any clause or example herein, in particular any of clauses 26 to 28, wherein the volume of each cellulose-based fiber after (c) is at least 10% less than the volume of each cellulose-based fiber before (c).

[0166] Clause 30. The method described in any clause or example herein, in particular any of clauses 20 to 29, wherein (a) comprises:

[0167] (a1) immersing at least a first portion of the block of natural plant material in a first solution to remove some of the lignin in the immersed first portion; and

[0168] (a2) After (a1), immersing at least the first portion in a second solution to remove remaining lignin in the immersed first portion.

[0169] Clause 31. The method of any clause or example herein, in particular Clause 30, wherein, after (a1) and before (a2), at least the first portion is washed with water to remove residues of the first solution.

[0170] Clause 32. The method of any clause or example herein, in particular any of clauses 30-31, wherein the first solution comprises formic acid peroxide (CH2O3).

[0171] Clause 33. The method of any clause or example herein, in particular any of clauses 30-32, wherein the second solution comprises sodium hydroxide (NaOH) or potassium hydroxide (KOH).

[0172] Clause 34. The method described in any clause or example herein, in particular any of clauses 30-31, wherein the first solution comprises a mixture of potassium hydroxide (KOH) and sodium sulfite (Na2SO3), a mixture of potassium hydroxide (KOH) and sodium sulfide (Na2S), a mixture of sodium hydroxide (NaOH) and sodium sulfite (Na2SO3), or a mixture of sodium hydroxide (NaOH) and sodium sulfide (Na2S).

[0173] Clause 35. The method of any clause or example herein, in particular any of clauses 30-32 and clause 34, wherein the second solution comprises a mixture of hydrogen peroxide (H2O2) and acetic acid (C2H4O2), or a mixture of hydrogen peroxide (H2O2) and formic acid (CH2O2).

[0174] Clause 36. The method of any clause or example herein, in particular any of clauses 20-35, further comprising infiltrating each cellulose-based fiber with a polymer to form a composite material.

[0175] Clause 37. The method of any clause or example herein, in particular any of clauses 20-36, further comprising embedding each cellulose-based fiber in a structural matrix to form a composite material.

[0176] Clause 38. The method of any clause or example herein, in particular clause 37, wherein the structural matrix comprises a polymer or concrete.

[0177] Clause 39. The method of any clause or example herein, in particular any of clauses 36-38, wherein the polymer comprises epoxy resin, polyvinyl alcohol (PVA), polyethylene glycol (PEO), polyamide (PA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), poly(m-phenylene isophthalamide) (PMIA), poly(p-phenylene terephthalamide) (PPTA), polyurethane (PU), polycarbonate (PC), polypropylene (PP), high-density polyethylene (HDPE), polystyrene (PS), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene terephthalate adipate (PBAT), poly(butylene succinate-co-adipate) (PBSA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(glycolic acid) (P GA), polypyrrole (PPy), polythiophene (PTh), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene vinyl alcohol (EVOH), poly(vinylidene chloride) (PVDC), poly(m-phenylene adipamide) (MXD6), polyethylene (PE), polyvinyl chloride (PVC), poly(methyl methacrylate) (PMMA), acrylonitrile-butadiene-styrene (ABS), polyimide (PI), polyethyleneimine (PEI), polylactic acid (PLA), octadecyltrichlorosilane (OTS), polyoctahedral silsesquioxane (POSS), p-methylstyrene (PMS), polydimethylsiloxane (PDMS), polyethylene naphthalate (PEN), a graft copolymer of acrylonitrile-butadiene-styrene-methyl methacrylate (ABSM), dodecyltrimethoxysilane (DTMS), rosin, chitin, chitosan, protain, vegetable oil, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination thereof.

[0178] Clause 40. The method of any clause or example herein, in particular any of clauses 38-39, wherein the concrete comprises Portland cement, agricultural concrete, magnesium carbonate (MgCO3), magnesium hydroxide (Mg(OH)2), or any combination thereof.

[0179] Clause 41. The method of any clause or example herein, in particular any of clauses 36-40, wherein the content of the plurality of cellulose-based fibers in the composite material is at least 0.1 wt% (eg, at least 0.5 wt%).

[0180] Clause 42. The method of any clause or example herein, in particular any one of clauses 20 to 41, wherein the natural plant material is a species in the order Poaceae.

[0181] Clause 43. The method of any clause or example herein, in particular any one of clauses 20 to 42, wherein the natural plant material is a species in the family Poaceae.

[0182] Clause 44. The method of any clause or example herein, in particular any one of clauses 20-43, wherein the natural plant material is natural grass.

[0183] Clause 45. The method of any clause or example herein, in particular any of clauses 20-44, wherein the natural plant material comprises bamboo, reed, sugar cane, corn, wheat, rice, jute, hemp, kenaf, ramie, banana, corn, wheat, rice, roselle, rattan, sorghum, sisal, palm, henna, abaca, pineapple, curaua, yucca, cabuya, pandanus, abaca, gladiolus or agave.

[0184] Item 46. The method of any item or example herein, in particular any of items 26-45, wherein, after (c), each cellulose-based fiber has a length of at least 5 cm and / or a maximum cross-sectional dimension (e.g. diameter) in a plane perpendicular to the length direction of at least 5 μm.

[0185] Clause 47. The method of any clause or example herein, in particular clause 46, wherein the length of each cellulose-based fiber after (b) is between 5 cm and 200 cm, inclusive.

[0186] Clause 48. The method of any clause or example herein, in particular any of clauses 46-47, wherein the maximum cross-sectional dimension (eg diameter) of each cellulose-based fiber after (b) is between 5 μm and 1 mm, inclusive.

[0187] Clause 49. The method of any clause or example herein, in particular any of clauses 46-48, wherein the maximum cross-sectional dimension of each cellulose-based fiber after (b) is at least 100 μm.

[0188] Clause 50. The method of any clause or example herein, in particular any one of clauses 26 to 49, wherein after (c), each cellulose-based fiber has a strength of at least 0.5 GPa·cm 3 / g (for example, ≥1GPa·cm 3 / g) specific strength, at least 40% (e.g., ≥50%) crystallinity, at least 0.5 GPa (e.g., ≥1 GPa) tensile strength, at least 20 GPa (e.g., ≥30 GPa or ≥60 GPa) Young's modulus, at least 0.8 g / cm 3 (e.g., ≥1 g / cm 3 ), or any combination of the foregoing.

[0189] Item 51. The method of any item or example herein, in particular any of items 26-50, wherein, after (c), each cellulose-based fiber has a cellulose content of at least 70 wt% (e.g., ≥85 wt%), a hemicellulose content of less than or equal to 10 wt% (e.g., ≤6 wt%), a lignin content of less than or equal to 10 wt% (e.g., ≤4 wt%), or any combination of the foregoing.

[0190] Item 52. The method described in any item or example herein, in particular any of items 20-51, further comprising providing a conductive additive, a magnetic additive, a piezoelectric material, a stimulus-responsive material, a catalytic material, or any combination of the foregoing on or within each cellulose-based fiber.

[0191] Clause 53. An engineered plant material formed by a method as described in any clause or example herein, in particular any one of clauses 20-52.

[0192] Clause 54. A composite material formed by a method as described in any clause or example herein, in particular any one of clauses 20-52.

[0193] in conclusion

[0194] Any features shown or described with respect to Figures 1-12 and clauses 1-54 may be combined with any other features shown or described with respect to Figures 1-12 and clauses 1-54 to provide materials, methods, devices, and embodiments not otherwise illustrated or specifically described herein. All features described herein are independent of each other and may be used in combination with any other features described herein, except where structurally impossible.

[0195] In view of the many possible embodiments to which the principles of the disclosed technology can be applied, it should be recognized that the illustrated embodiments are only preferred examples and should not be considered as limiting the scope of the disclosed technology. Instead, the scope is defined by the following claims. Therefore, we request protection for all that falls within the scope and spirit of these claims.

Claims

1. An engineered plant material comprising: one or more substantially delignified cellulose-based macrofibers chemically extracted intact from the lignin and hemicellulose matrix in the microstructure of a mass of natural bamboo, said lignin and hemicellulose matrix connecting the microfibrils of the one or more macrofibers to the thin-walled cells, Each cellulose-based macrofiber is unique and different from any other cellulose-based macrofiber extracted from natural bamboo. Each cellulose-based macrofiber has a moisture content of less than or equal to 10 wt %, Each cellulose-based macrofiber has a length of at least 5 cm, a diameter of at least 100 μm, and a density of at least 1 g / cm 3 ,as well as Each cellulose-based macrofiber exhibits a tensile strength of at least 1 GPa.

2. A composite material comprising: a plurality of substantially delignified cellulose-based macrofibers, each cellulose-based macrofiber being chemically extracted intact from a matrix of lignin and hemicellulose in the microstructure of a respective mass of natural bamboo, the matrix of lignin and hemicellulose connecting microfibrils of one or more macrofibers to thin-walled cells; and The polymer permeates each cellulose-based macrofiber. Each cellulose-based macrofiber is unique and different from any other cellulose-based macrofiber extracted from natural bamboo. Each cellulose-based macrofiber has a moisture content of less than or equal to 10 wt %, Each cellulose-based macrofiber has a length of at least 5 cm, a diameter of at least 100 μm, and a density of at least 1 g / cm 3 ,as well as Each cellulose-based macrofiber exhibits a tensile strength of at least 1 GPa.

3. A composite material comprising: structural matrix; as well as a plurality of substantially delignified cellulose-based macrofibers disposed within the structural matrix, each cellulose-based macrofiber being chemically extracted intact from a matrix of lignin and hemicellulose in the microstructure of a corresponding mass of natural bamboo, the matrix of lignin and hemicellulose connecting microfibrils of one or more macrofibers to parenchyma cells, Each cellulose-based macrofiber is unique and different from any other cellulose-based macrofiber extracted from natural bamboo. Each cellulose-based macrofiber has a moisture content of less than or equal to 10 wt %, Each cellulose-based macrofiber has a length of at least 5 cm, a diameter of at least 100 μm, and a density of at least 1 g / cm 3 ,as well as Each cellulose-based macrofiber exhibits a tensile strength of at least 1 GPa.

4. The material of claim 3, wherein the structural matrix comprises a polymer or concrete.

5. The material according to any one of claims 2 and 4, wherein the polymer comprises epoxy resin, polyvinyl alcohol (PVA), polyethylene glycol (PEO), polyamide (PA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polymethylene isophthalamide (PMIA), polyp-phenylene terephthalamide (PPTA), polyurethane (PU), polycarbonate (PC), polypropylene (PP), high-density polyethylene (HDPE), polystyrene (PS), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene terephthalate adipate (PBAT), poly(succinic acid-co-adipate) (PBSA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(glycolic acid) (PGA), polypyrrole ( PPy), polythiophene (PTh), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene-vinyl alcohol (EVOH), poly(vinylidene chloride) (PVDC), poly(m-phenylene adipamide) (MXD6), polyethylene (PE), polyvinyl chloride (PVC), poly(methyl methacrylate) (PMMA), acrylonitrile-butadiene-styrene (ABS), polyimide (PI), polyethyleneimine (PEI), polylactic acid (PLA), octadecyltrichlorosilane (OTS), polyoctahedral silsesquioxane (POSS), p-methylstyrene (PMS), polydimethylsiloxane (PDMS), polyethylene naphthalate (PEN), a graft copolymer of acrylonitrile-butadiene-styrene-methyl methacrylate (ABSM), dodecyltrimethoxysilane (DTMS), rosin, chitin, chitosan, protain, vegetable oil, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination thereof.

6. The material of claim 4, wherein the concrete comprises Portland cement, agricultural concrete, magnesium carbonate (MgCO3), magnesium hydroxide (Mg(OH)2), or any combination thereof.

7. The material according to any one of claims 2-3, wherein the content of the plurality of cellulose-based macrofibers in the composite material is at least 0.1 wt%.

8. The material according to any one of claims 1 to 3, wherein: The microstructure of the natural bamboo has a cavity at least partially formed by a matrix and thin-walled cells; and The one or more substantially delignified cellulose-based macrofibers lack such lumens.

9. The material according to any one of claims 1 to 3, wherein the length of each cellulose-based macrofiber is between 5 cm and 200 cm, inclusive.

10. The material of any one of claims 1-3, wherein each cellulose-based macrofiber has a crystallinity of at least 50%.

11. The material of any one of claims 1-3, wherein each cellulose-based macrofiber has a Young's modulus of at least 60 GPa.

12. The material of any one of claims 1-3, wherein each cellulose-based macrofiber has a cellulose content of at least 70 wt%, a hemicellulose content of less than or equal to 10 wt%, a lignin content of less than or equal to 10 wt%, or any combination thereof.

13. The material according to any one of claims 1-3, wherein provided on or within each cellulose-based macrofiber is a conductive additive, a magnetic additive, a piezoelectric material, a stimulus-responsive material, a catalytic material, or any combination thereof.

14. The material according to any one of claims 1 to 3, wherein the density of each cellulose-based macrofiber is 1.45 g / cm 3 .

15. The material according to any one of claims 1 to 3, wherein: The microfibers in natural bamboo have an aligned and ordered structure; and Each cellulose-based macrofibril retains the aligned, ordered structure of the microfibrils.

16. A method comprising: (a) subjecting a block of natural bamboo to one or more chemical treatments to remove substantially all lignin therefrom, the natural bamboo having a microstructure having a plurality of cellulose-based macrofibrils, thin-walled cells, and a matrix of lignin and hemicellulose connecting the microfibrils of the cellulose-based macrofibrils to the thin-walled cells, the one or more chemical treatments being effective to dissolve the matrix and break down the thin-walled cells, thereby releasing the cellulose-based macrofibrils; (b) after (a), extracting the plurality of cellulose-based macrofibrils from the chemically treated mass as individual, intact cellulose-based macrofibrils that are separate and distinct from one another; and (c) drying the cellulose-based macrofibers such that evaporation of water from each cellulose-based macrofiber causes the macrofiber to self-densify, wherein, after (a), each cellulose-based macrofiber is substantially delignified, and Where, after (c): Each cellulose-based macrofiber has a moisture content of less than or equal to 10 wt %, Each cellulose-based macrofiber has a length of at least 5 cm, a diameter of at least 100 μm, and a density of at least 1 g / cm 3 ,as well as Each cellulose-based macrofiber exhibits a tensile strength of at least 1 GPa.

17. The method of claim 16, wherein: Prior to (a), the microstructure of the natural bamboo has a cavity at least partially formed by a matrix and thin-walled cells; as well as After (a), the chemically treated block lacks such cavities.

18. The method according to claim 16, wherein the density of each cellulose-based macrofiber is 1.45 g / cm 3 .

19. The method of claim 16, wherein (b) comprises agitating the chemically treated mass in the solution.

20. The method of claim 16, wherein at least one of the one or more chemical treatments comprises partial or complete immersion in one or more chemical solutions.

21. The method of claim 20, wherein the one or more chemical solutions include an alkaline solution.

22. The method of claim 20, wherein the one or more chemical solutions include sodium hydroxide (NaOH), lithium hydroxide (LiOH), potassium hydroxide (KOH), sodium sulfite (Na2SO3), sodium sulfide (Na2S), Na n S (where n is an integer), urea (CH4N2O), sodium bisulfite (NaHSO3), sulfur dioxide (SO2), anthraquinone (C 14 H8O2), methanol (CH3OH), ethanol (C2H5OH), butanol (C4H9OH), formic acid (CH2O2), hydrogen peroxide (H2O2), acetic acid (CH3COOH), butyric acid (C4H8O2), formic acid peroxide (CH2O3), acetic acid peroxide (C2H4O3), ammonia (NH3), p-toluenesulfonic acid (p-TsOH), sodium hypochlorite (NaClO), sodium chlorite (NaClO2), chlorine dioxide (ClO2), chlorine (Cl2), or any combination thereof.

23. The method of claim 16, wherein after (a), the plurality of cellulose-based macro-fibers remain attached to a base of the natural bamboo, and the extracting of (b) comprises severing the cellulose-based macro-fibers from the base.

24. The method of claim 16, wherein the drying of (c) comprises exposure to air or gas flow, exposure to a stagnant volume of air or gas, exposure to a vacuum, exposure to room temperature, heating to a temperature above room temperature, or any combination thereof.

25. The method of claim 16, wherein the volume of each cellulose-based large fiber after (c) is at least 10% less than the volume of each cellulose-based large fiber before (c).

26. The method of claim 16, wherein (a) comprises: (a1) immersing at least a first portion of the block of natural bamboo in a first solution to remove some lignin in the immersed first portion; and (a2) After (a1), immersing at least the first portion in a second solution to remove remaining lignin in the immersed first portion.

27. The method according to claim 26, wherein: After (a1) and before (a2), at least the first portion is washed with water to remove residues of the first solution.

28. The method of claim 26, wherein the first solution comprises formic acid peroxide (CH2O3).

29. The method of any one of claims 26 and 28, wherein the second solution comprises sodium hydroxide (NaOH) or potassium hydroxide (KOH).

30. The method of claim 26, wherein the first solution comprises a mixture of potassium hydroxide (KOH) and sodium sulfite (Na2SO3), a mixture of potassium hydroxide (KOH) and sodium sulfide (Na2S), a mixture of sodium hydroxide (NaOH) and sodium sulfite (Na2SO3), or a mixture of sodium hydroxide (NaOH) and sodium sulfide (Na2S).

31. The method of any one of claims 26, 28 and 30, wherein the second solution comprises a mixture of hydrogen peroxide (H2O2) and acetic acid (C2H4O2), or a mixture of hydrogen peroxide (H2O2) and formic acid (CH2O2).

32. The method of claim 16, further comprising infiltrating a polymer into each of the cellulose-based macrofibers to form a composite material.

33. The method of claim 16, further comprising embedding each cellulose-based macro-fiber in a structural matrix to form a composite material.

34. The method of claim 33, wherein the structural matrix comprises a polymer or concrete.

35. The method of any one of claims 32 and 34, wherein the polymer comprises an epoxy resin, polyvinyl alcohol (PVA), polyethylene glycol (PEO), polyamide (PA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyacrylonitrile (PAN), polycaprolactam (PA6), polymethylene isophthalamide (PMIA), polyp-phenylene terephthalamide (PPTA), polyurethane (PU), polycarbonate (PC), polypropylene (PP), high-density polyethylene (HDPE), polystyrene (PS), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene terephthalate adipate (PBAT), poly(butylene succinate-co-adipate) (PBSA), polyhydroxybutyrate (PHB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(glycolic acid) (PGA), polypyrrolidone (PP), polyvinyl alcohol (PVA ... poly(vinylidene fluoride) (PPy), polythiophene (PTh), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene-vinyl alcohol (EVOH), poly(vinylidene chloride) (PVDC), poly(m-phenylene adipamide) (MXD6), polyethylene (PE), polyvinyl chloride (PVC), poly(methyl methacrylate) (PMMA), acrylonitrile-butadiene-styrene (ABS), polyimide (PI), polyethyleneimine (PEI), polylactic acid (PLA), octadecyltrichlorosilane (OTS), polyoctahedral silsesquioxane (POSS), p-methylstyrene (PMS), polydimethylsiloxane (PDMS), polyethylene naphthalate (PEN), a graft copolymer of acrylonitrile-butadiene-styrene-methyl methacrylate (ABSM), dodecyltrimethoxysilane (DTMS), rosin, chitin, chitosan, protain, vegetable oil, carboxymethyl cellulose, cellulose acetate, starch, agar, alginic acid, or any combination thereof.

36. The method of claim 34, wherein the concrete comprises Portland cement, agricultural concrete, magnesium carbonate (MgCO3), magnesium hydroxide (Mg(OH)2), or any combination thereof.

37. The method of any one of claims 32-33, wherein the composite material comprises a plurality of cellulose-based macro fibers in an amount of at least 0.1 wt%.

38. The method of claim 16, wherein each of the cellulose-based macro-fibers after (c) has a length between 5 cm and 200 cm, inclusive.

39. The method of claim 16, wherein: After (c), each cellulose-based macro-fiber has a Young's modulus of at least 60 GPa.

40. The method of claim 16, wherein: After (c), each of the cellulose-based macrofibers has a crystallinity of at least 50%.

41. The method of claim 16, wherein: Prior to (a), the microfibers in natural bamboo have an aligned and ordered structure; and After (c), each cellulose-based macrofibril retains the aligned and ordered structure of the microfibrils.

42. The method of claim 16, wherein: After (c), each cellulose-based macrofiber has a cellulose content of at least 70 wt%, a hemicellulose content of less than or equal to 10 wt%, a lignin content of less than or equal to 10 wt%, or any combination thereof.

43. The method of claim 16, further comprising providing a conductive additive, a magnetic additive, a piezoelectric material, a stimuli-responsive material, a catalytic material, or any combination thereof on or within each cellulose-based macrofiber.

44. An engineered plant material formed by the method of any one of claims 16-43.

45. A composite material formed by the method of any one of claims 16-43.

Citation Information

Patent Citations

  • Delignified wood materials, and methods for fabricating and use thereof

    WO2019055789A1